2023
DOI: 10.1109/jphot.2023.3281134
|View full text |Cite
|
Sign up to set email alerts
|

Development of Grating for the Optical Addressing of Sr+ Ions With Data Analysis Techniques

Abstract: In this study, SiN-based gratings with various radius of curvature (r) are designed and fabricated for the optical addressing of trapped Sr + ion. The beam width of the light coupled out from the gratings is investigated using a self-developed Pythonbased data analysis technique. It is found that the r values have insignificant influence on the beam width along x-axis; whereas the beam waist along y-axis reduces from 13.96 to 12.3 µm as r increases from 15 to 20 µm, then increases gradually to 20.51 µm as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…From our previous studies, we observed that changes in R values varies the shape of the corresponding beam profiles along y-axis, with limited impact on the beam profiles along x-axis (axis reference: Fig. 1(a)) [20,23]. As shown in Fig.…”
Section: Background and Motivationmentioning
confidence: 83%
See 4 more Smart Citations
“…From our previous studies, we observed that changes in R values varies the shape of the corresponding beam profiles along y-axis, with limited impact on the beam profiles along x-axis (axis reference: Fig. 1(a)) [20,23]. As shown in Fig.…”
Section: Background and Motivationmentioning
confidence: 83%
“…In optical addressing of trapped ions, the application of gratings, in place of traditional optical fiber, greatly reduces the formfactor of ion trap quantum computing devices, and further enhances the manufacturability of quantum computing chips. In our previous works, we have attempted to improve the focusing of chip-to-free-space light by modifying the grating designs, such as varying the radius of curvature (R) of the pitch structure in gratings [20,21], or introducing mixed pitch gratings for enhanced focusing [22]. The R values of grating couplers are illustrated in Fig.…”
Section: Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations